The Land of the Future: British Accounts of the USA at the Turn of the Nineteenth Century - David Seed (European Journal of American Studies)
This article examines the ways in which British travelers to the USA at the end of the nineteenth and beginning of the twentieth centuries articulated their different perceptions of a nation which was emerging as a major imperial competitor. Characteristically these responses showed an ambivalent tension between respect for the growing commercial energy of the USA and a suspicion that it was posing an increasing threat to British national self-perception. Works examined here include those which attempt to yoke together the two nations in a common “Anglo-Saxon” destiny. The essay analyzes the expressive means used by writers to depict the USA as a culture of the future. The discussion includes famous figures like Rudyard Kipling and H.G. Wells, but also covers a range of turn-of-the-century speculative writers like the journalist W.T. Stead.